Identification of a diagnostic structural motif reveals a new reaction intermediate and condensation pathway in kraft lignin formation - Lancefield, Christopher S.; Wienk, Hans L. J.; Boelens, Rolf; Weckhuysen, Bert M.; Bruijnincx, Pieter C. A. (Chemical science (Cambridge), 2018)
Kraft lignin, the main by-product of the pulping industry, is an abundant, yet highly underutilized renewable aromatic polymer. During kraft pulping, the lignin undergoes extensive structural modification, with many labile native bonds being replaced by new, more recalcitrant ones. Currently little is known about the nature of those bonds and linkages in kraft lignin, information that is essential for its efficient valorization to renewable fuels, materials or chemicals. Here, we provide detailed new insights into the structure of softwood kraft lignin, identifying and quantifying the major native as well as kraft pulping-derived units as a function of molecular weight. De novo synthetic kraft lignins, generated from (isotope labelled) dimeric and advanced polymeric models, provided key mechanistic understanding of kraft lignin formation, revealing different process dependent reaction pathways to be operating. The discovery of a novel kraft-derived lactone condensation product proved diagnostic for the identification of a previously unknown homovanillin based condensation pathway. The lactone marker is found in various different soft- and hardwood kraft lignins, suggesting the general pertinence of this new condensation mechanism for kraft pulping. These novel structural and mechanistic insights will aid the development of future biomass and lignin valorization technologies.